Hukuman Mati Di Indonesia Menurut Perspektif Alkitab dan Implikasi Bagi Penegak Hukum Kristen - Morris Phillips Takaliuang (Sekolah Tinggi Teologi Simpson, 2020)
Provisions and implementation of the death penalty, is a serious and very severe law for perpetrators who are considered to have committed serious and serious violations before the law. The Indonesian state still holds and carries out such a death sentence, as regulated in the Criminal Code. There are three stages in the Bible regarding the provisions and execution of the death penalty: (1) The death penalty applies to people who sin directly to God, such as worshiping idols, turning to the spirits of the dead, chanting the name of God carelessly and not keeping the Sabbath day holy, (2 ) The death penalty applies to people who commit sins against others such as killing and all the acts of adultery, and (3) The provisions and execution of the death penalty are null and void for anyone who is in faith and obedience to Christ. The task as a Christian and church law enforcer is to bring sinners to believe and be in fellowship with Christ. For